Serum periostin relates to type‐2 inflammation and lung function in asthma: Data from the large population‐based cohort Swedish GA(2)LEN - James, A.; Janson, C.; Malinovschi, A.; Holweg, C.; Alving, K.; Ono, J.; Ohta, S.; Ek, A.; Middelveld, R.; Dahlén, B.; Forsberg, B.; Izuhara, K.; et al. (Allergy (Copenhagen), 2017)
Background Periostin has been suggested as a novel, phenotype‐specific biomarker for asthma driven by type 2 inflammation. However, large studies examining relationships between circulating periostin and patient characteristics are lacking and the suitability of periostin as a biomarker in asthma remains unclear. Aim To examine circulating periostin in healthy controls and subjects with asthma from the general population with different severity and treatment profiles, both with and without chronic rhinosinusitis (CRS), in relation to other biomarkers and clinical characteristics. Methods Serum periostin was examined by ELISA in 1100 subjects aged 17‐76 from the Swedish Global Allergy and Asthma European Network (GA(2)LEN) study, which included 463 asthmatics with/without chronic rhinosinusitis (CRS), 98 individuals with CRS only, and 206 healthy controls. Clinical tests included measurement of lung function, Fraction of exhaled NO (FeNO), IgE, urinary eosinophil‐derived neurotoxin (U‐EDN), and serum eosinophil cationic protein (S‐ECP), as well as completion of questionnaires regarding respiratory symptoms, medication, and quality of life. Results Although median periostin values showed no differences when comparing disease groups with healthy controls, multiple regression analyses revealed that periostin was positively associated with higher FeNO, U‐EDN, and total IgE. In patients with asthma, an inverse relationship with lung function was also observed. Current smoking was associated with decreased periostin levels, whereas increased age and lower body mass index (BMI) related to higher periostin levels in subjects both with and without asthma. Conclusion We confirm associations between periostin and markers of type 2 inflammation, as well as lung function, and identify novel constitutional factors of importance to the use of periostin as a phenotype‐specific biomarker in asthma.